Perception of the Risks Associated with Impaired Driving and Effects on Driving Behavior - Claude Fluet
This research studies the perception of the risks associated with impaired driving-probability of being apprehended or of having an accident-and the relation between the perception of risks and driving behavior. The most important determinants of perceptual biases are age, an accumulation of violations in the year preceding the survey, being a non-drinker, knowledge of the legal alcohol limit for driving, opinion about zero tolerance for impaired driving, and family income. Perceptual biases are shown to influence driving behavior, as captured by drivers' accumulated violations, demerit points and bodily injury accidents, in the years preceding and in the year following the survey. In conclusion, we analyze the results in terms of public policy for road safety.Risk perception, impaired driving, driving behavior, traffic violation, road accident, regulation, public policy